Peran Konselor dalam Memberikan Pemahaman Pubertas Melalui Layanan Orientasi di SMPN 02 Kota Jambi - Rahmayanty, Dinny; Aisah, Siti; Artita, Exsa; Afriyani, Windi (Nuban Jaggadhita Center, 2023)
Purpose: The purpose of this service is so that every student is able to have an understanding regarding puberty and can benefit from the material that has been introduced through orientation services. Methodology: The achievements of this activity are reports and documentation of the implementation of orientation services dedicated to the Faculty of Teaching and Education, University of Jambi. Findings: This devotional article discusses the role of counselors through orientation services in providing an understanding of puberty to SMPN 02 Jambi City students. This is done because there are many teenagers who do not understand the developments that occur in the body during puberty and PLK-PLS Guidance and Counseling students at PKBI Jambi Region are moved to carry out these activities. As that student guidance and counseling out the duties of a counselor at school. With orientation services, it is hoped that students’ understanding of puberty will be created.